IMPLEMENTASI PENDEKATAN KOMUNIKATIF INTEGRATIF DALAM PEMBELAJARAN MUHĀDATSAH DI MA’HAD ‘ALY NURUL JADID - Jamila, Nafissatul; Khotimah, Isnol (STIQ Amuntai, 2024)
Communication skills are very important in everyday life to convey information, expressions, thoughts, and ideas to other people. This study uses a qualitative method. The data used in this research was taken from observation, in-depth interviews, and documentation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The introduction of an integrative communicative approach to Muhadatsah learning at Ma'had ‘Aly Nurul Jadid is an innovative step in improving the students' Arabic language skills. This approach comprehensively integrates aspects of communication and language skills, thereby enabling students to develop their speaking skills more effectively. As an Islamic educational institution, Ma'had ‘Aly realizes the importance of learning Arabic to understand religious texts. With integrative communicative-based Muhadatsah learning, it can create a learning environment that supports direct interaction between musyrifaat and students, helping students understand and use Arabic in everyday contexts. This research aims to determine the application of the muhadatsah method in collaboration with an integrative communicative approach so as to obtain maximum results, namely creating students who are proficient in understanding and communicating using Arabic, so that students are able to master and apply the language well in various communication situations in real life. In this way, the application of a communicative approach in muhadatsah learning can form students who are capable of using Arabic and are able to apply it in real life, which is relevant to everyday life.